Analysis of the Tsunami Evacuation Route in Kunjir Village and Way Muli Village, South Lampung Regency - Any Nurhasanah; Muhammad Imam Riady; Aprizal Aprizal (Jurnal Teknik Sipil, 2020)
This research was conducted to analyze the effectiveness of existing evacuation routes in Kunjir Village and Way Muli Village by calculating the level of safety of the population when evacuating in the event of a tsunami disaster. The data used are direct field observations, topographic maps derived from aerial photo mapping results, existing conditions of evacuation routes, gathering conditions, evacuation direction signs, and data on tsunami wave heights that may occur in the study area. We analyze the tsunami disaster evacuation route using Network Analyst in ArcGIS. Furthermore, the evacuation route is determined which has a road width of more than 2 m so that not all roads in both villages are used as evacuation routes. In determining the evacuation point modeling tsunami inundation is used with a wave height of 4 m. Later the route and direction of the nearest evacuation route will be known to the safe evacuation point. Based on the results of the study, the number of evacuation routes in Way Muli Village amounted to 5 with 4 site points while in Kunjir Village there were 7 with 4 site points that could be used as evacuation sites. The farthest distance from the evacuation route to the evacuation site in Way Muli Village is 441.5 m with a travel time of 4 minutes and for Kunjir Village is 704.3 m with a travel time of 6.38 minutes.